Universal blood-borne virus screening in patients with severe mental illness managed in an outpatient clozapine clinic: uptake and prevalence. (April 2020) - Williams, Jacob; Barclay, Marilyn; Omana, Chester; Buten, Sara; Post, Jeffrey J
Objective: Patients with a severe mental illness have higher rates of infection with blood-borne viruses (BBVs) but are less likely to access testing and treatment. Enhanced testing of this population is therefore warranted. Methods: In this single centre, prospective study, we sought to offer testing for BBVs to all patients who attended an appointment in the clozapine clinic (CC) over a six-month period. Those who consented were tested for HIV antigen/antibody, hepatitis C virus (HCV) antibody and hepatitis B virus surface antigen (HBsAg). Results: During the study period, 192 patients attended an appointment, of which 164 were offered testing. Of those, 134 (81.7%) accepted and 30 declined. Among patients who agreed to be tested, results were returned for 96 (71.6%). There were no positive results for HBsAg or HIV. Seven patients (7.2%) were positive for HCV antibody. Of those, three were newly identified exposures of which two were found to be chronically infected and were referred for treatment. Conclusion: A routine offer of BBV testing for people with severe mental illness in the outpatient setting is feasible and may detect treatable infections.